Breastfeeding Exclusive Status and Stunting Incidence Among Children Aged 24-36 Months in West Gunungsitoli, Nias - Tarigan, Yenni Gustiani; Etty, Christina Roos; Purba, Ivan Elisabeth; Riaprilany, Nibenia (REAL in Nursing Journal, 2024)
Background: Stunting occurs when the fetus is still in the womb and only appears when the child is two years old. Stunting in toddlers needs special attention because it can hinder children's physical and mental development. Stunting is associated with an increased risk of morbidity and death as well as hampered growth of motor and mental abilities which carries a risk of decreased intellectual abilities, productivity and increased risk of degenerative diseases. The study objective was to determine the relationship between exclusive breastfeeding and stunting incidence among children aged 24 to 36 months in West Gunungsitoli. Methods: This was observational study with a cross sectional design. The study population was all mothers who had stunted toddlers aged 24 to 36 months with sample of 42 respondents. We used univariate and bivariate analysis for data analysis. Chi square test was used to analyze the relationship with α =0.05. Results: The results of this study were 78.6% of stunted toddlers were not given exclusive breast milk and only 21.4% were given. There were 69% of stunted toddlers had a short height and 31 % toddlers with very short height. Conclusin: However, there was a relationship between exclusive breastfeeding and stunting incident in West Gunungsitoli with a p-value=0.032. Therefore, it is recommended that all mothers in West Gunungsitoli need to be given education about the importance of giving exclusive breast milk to babies.Keywords: Exclusive breastfeeding, stunting, toddlers.